A novel 3-D pulsating heat pipe module for high heat-flux applications. (25th June 2023) - Zamanifard, Abdolmajid; Muneeshwaran, M.; Wang, Yu-Hsin; Wang, Chi-Chuan
Highlights: A novel 3-D module of the pulsating heat pipe is proposed. The PHP is investigated experimentally in a wide range of heat flux 100–800 W. The effect of the different filling ratios between 25% and 60% is examined. The proposed module could dissipate heat around 70 W∙cm −2 . Abstract: This study proposed a novel pulsating heat pipes (PHP) for high-flux thermal module. According to the open literature, the maximum value of the heat flux is 23.7 W∙cm −2 handled by PHP, which is far behind industry requirements. Therefore, the present study proposes a novel 3D PHP suitable for high heat-flux applications. The PHP were experimentally tested for different working fluids, including methanol and water. Furthermore, the experiments were performed to analyze the influence of various operating parameters, such as filling ratio (25–60%), heat load (100–800 W), and air flow rate 100–250 cubic feet per minute (CFM). The results showed that this PHP can sustain a heat flux up to 70 W∙cm −2 with the maximum case temperature under 80 °C, which is approximately three times higher than the available literature. Furthermore, the performance of the PHP module was compared against the commercial module with wicked heat pipe. The PHP exhibited about 7% higher heat dissipation compared to the commercial module. Since the proposed module uses simple copper tubes in its construction over the wicked structure used in commercial module, the novel 3D PHP module provides additional economic and mass production capability.